Landscape of rare‐allele variants in cultivated and wild soybean genomes - Zhi Liu; Xiaolei Shi; Qing Yang; Ying Li; Chunyan Yang; Mengchen Zhang; Yong‐Qiang Charles An; Henry T. Nguyen; Long Yan; Qijian Song (The Plant Genome)
Abstract Rare‐allele variants are important for crop improvement because they can be linked to important traits. However, genome‐wide distribution and annotation of rare‐allele variants have not been reported. We analyzed sequencing data from 1556 soybean accessions and found 6,533,419 rare‐allele variants in Glycine max and 941,274 in Glycine soja populations. Although the total number of variants was 20% less in G. max than G. soja, the number of rare‐allele variants in G. max was six times that in G. soja. Among the rare‐allele variants in G. max, 19.16% were novel mutations that did not exist in G. soja. Domestication and artificial selection have not only reduced overall genetic diversity but also the frequency of variants of cultivated soybean. Rare‐allele variants were mainly located in intergenic and noncoding regions rather than coding regions, and in heterochromatin regions rather than euchromatic regions. There were 121,450 rare‐allele variations in 36,213 G. max genes and 20,645 in 12,332 G. soja genes, resulting in nonsynonymous, stop gain or stop loss mutations. This study provided the first comprehensive understanding of rare‐allele variants in wild and cultivated soybean genomes and its potential impact on gene functions. This information will be valuable for future studies aimed at improving soybean varieties, as these variants may help reveal the underlying mechanisms controlling traits and have the potential to improve stress resistance, yield, and adaptability to environments.